Taxonomic authority in endemic freshwater fishes of a Mediterranean biodiversity hotspot: From expeditionary natural history to systematics - PERDIKARIS, COSTAS; KOUTSIKOS, NICHOLAS; VARDAKAS, LEONIDAS (Mediterranean Marine Science, 2026)
Taxonomy has long been guided by natural scientists whose choices, methods, and values shape how biodiversity is named and used today. This study reconstructs the making of one regional fauna, the endemic freshwater fishes now recognized from the territory of the modern Greek state, focusing on the researchers who collected and described these species and how they shaped freshwater fish systematics. We review sources screened through 2025 and analyze the description record of endemic species, which extends from 1837 to 2017. Using a dataset of 91 valid endemic species and 47 scientists, we examine who named what, when, and under which institutional, linguistic, and political conditions. For each species, we traced nomenclatural history, type locality, publication type and language; for each author, we compiled demographics, nationality, affiliations, discipline, and fieldwork activity, cross-checking multiple sources and, where possible, verifying details directly with living authors. Species descriptions accumulated in uneven pulses. The slow early phase was dominated by non-domestic expeditions (1830s-1900s). A pronounced interwar peak (1920s-1930s) was led by Balkan and Greek scientists, followed by wartime contraction (1940s). Renewed momentum followed the post-war decades and especially after 2000 as analytical tools improved. Authorship was highly skewed, with four prolific contributors (Karaman, Stephanidis, Economidis and Kottelat) producing nearly two-thirds of the names. Publication practices shifted gradually from monographs to serials, and from German to English, while about three-quarters of original combinations changed at least once. Overall, this study offers a people-centred baseline for Greek freshwater ichthyology, honoring its pioneers and showing how methods, taxonomic concepts, and cultural influences co-evolved. Within this context, it aims also to inform broader discussions on how taxonomic knowledge is formed and sustained within specific historical settings.